Optimising patients with long-term spinal cord injury for nephrectomy: A review of pre-, peri- and post-operative factors to safeguard outcomes. (March 2021) - Donati-Bourne, J; Kasmani, Z; Mohamed, WGE; Pillai, P; O'Dair, J; Bhatt, RI
Objectives: To review the potential challenges a urologist may encounter when embarking on simple/partial/radical nephrectomy in patients with long-term spinal cord injury and propose strategies to pre-empt and manage these. Materials and methods: Comprehensive literature review via PubMed, MEDLINE® and Google™ Scholar searching for relevant scientific articles published to date in English. Recommendations for strategies to safeguard surgical outcomes discussed with a panel of experienced upper-tract urologists. Results: Pre-operative considerations: - urethral assessment via flexible cystoscopy due to higher incidence of urethral pathology in spinal cord injury; - assessing for chronic constipation and distended bowel; and - considering glomerular filtration rate assessment by radio-isotope techniques, such as 51 chromium-EDTA Peri-operative considerations: - adequate theatre staffing for safe patient transfer; and - planned choice of incision, due to higher incidence of previous abdominal surgery, stoma bags and/or foreign body devices. Post-operative considerations: - ensuring attending medical staff are trained to recognise autonomic dysreflexia; - early re-mobilisation with physiotherapists experienced in treating spinal cord injury; and - attentive antibiotic stewardship due to higher risk of hospital-acquired or urinary infections Conclusions: Patients with long-term spinal cord injury pose significant potential challenges in the pre-, peri- and post-operative stages of nephrectomy. Familiarisation and optimisation of such factors is recommended to safeguard outcomes. Level of evidence: Not applicable for this multicentre audit.